Secreted sphingomyelins modulate low mammary cancer incidence observed in certain mammals - Melissa M. Ledet (Nature Portfolio, 2020)
Abstract Determining mechanisms that naturally protect species from developing cancer is critical in order to prevent and treat cancer. Here, we describe a novel cancer-suppressing mechanism, via the secretion of bioactive factors by mammary cells, that is present in domesticated mammals with a low mammary cancer incidence. Specifically, these bioactive factors induced triple-negative breast cancer cell (TNBC) death in vitro and reduced tumorigenicity in a xenograft TNBC mouse model in vivo. RNA deep sequencing showed significant downregulation of genes associated with breast cancer progression in secretome-cultured TNBC cells. Further in-depth multi-omics analysis identified sphingomyelins as key secreted factors, and their role was confirmed via inhibition of the sphingomyelin signaling pathway. We speculate that secreted sphingomyelins in the mammary gland of mammals with a naturally low incidence of mammary cancer mediate the elimination of cancer cells. This study contributes to the growing list of protective mechanisms identified in cancer-proof species.